A post-hoc subgroup analysis of data from a six month clinical trial comparing the efficacy and safety of losmapimod in moderate-severe COPD patients with ≤2% and >2% blood eosinophils. Issue 7 (July 2015) - Marks-Konczalik, Joanna; Costa, Maria; Robertson, Jon; McKie, Elizabeth; Yang, Shuying; Pascoe, Steven
Summary: Background: A six month study of the p38 MAPK inhibitor, losmapimod, suggested a trend in reducing COPD exacerbations with the 15 mg twice daily dose. Objective and methods: Using data from this study which evaluated the efficacy of twice daily losmapimod, 2.5 mg, 7.5 mg, and 15 mg, versus placebo in patients with moderate-to-severe COPD, we analysed the effect of losmapimod in reducing the rate of moderate/severe exacerbations in patient subgroups with ≤2% and >2% blood eosinophils at baseline. Lung function, fibrinogen and hsCRP were also evaluated. Results: In the ≤2% eosinophil subgroup, there was an exposure-related reduction in the rate of moderate/severe exacerbations with losmapimod relative to placebo (losmapimod 15 mg: 55% reduction; losmapimod 7.5 mg: 29%; losmapimod 2.5 mg: 10%); with the 15 mg dose reaching statistical significance (15 mg/placebo mean rate ratio [95% CI]: 0.45 [0.22; 0.90]). There was also an improvement in lung function with 15 mg losmapimod over Weeks 1–12. No improvement in the rate of moderate/severe exacerbations or post-bronchodilator FEV1 was observed for subjects treated with Losmapimod compared to placebo in the patient subgroup with blood eosinophils >2% at baseline. Transient reductions in fibrinogen and hsCRP were observed with losmapimod 7.5 mg and 15 mg in both eosinophil subgroups. Conclusions: These findings indicate eosinophil-related heterogeneity within COPD and suggest that losmapimod could be a potential therapy to reduce exacerbations in COPD patients with eosinophil levels ≤2%. This needs to be explored further in a prospectively designed study with pre-specified criteria for blood eosinophil subgroups in COPD patients.